2022
DOI: 10.1039/d2ra05779d
|View full text |Cite
|
Sign up to set email alerts
|

Is degradation of dyes even possible without using photocatalysts? – a detailed comparative study

Abstract: Degradation of cationic dyes through self generation of ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…So, the test for total organic carbon was used to analysis the percentage of mineralization of dyes. TOC test was performed using Tekmar Dohrmann Apollo 9000 analyzer for 5 h. Results (Figure 9) found that the TOC percentage for DY 12, CR, and MG dyes were 35%, 39%, and 41%, respectively 24,51,52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the test for total organic carbon was used to analysis the percentage of mineralization of dyes. TOC test was performed using Tekmar Dohrmann Apollo 9000 analyzer for 5 h. Results (Figure 9) found that the TOC percentage for DY 12, CR, and MG dyes were 35%, 39%, and 41%, respectively 24,51,52 …”
Section: Resultsmentioning
confidence: 99%
“…Results (Figure 9) found that the TOC percentage for DY 12, CR, and MG dyes were 35%, 39%, and 41%, respectively. 24,51,52 Mineralization study of selected dyes was also investigated by determination of chemical oxygen demand. The Spectroquant TR…”
Section: Toc and Cod Measurementsmentioning
confidence: 99%
“…The investigation into the thermodynamics of photocatalytic self-degradation of DPP was conducted to examine the catalysis mechanism. 50 Specifically, the degradation of TDPP and PhDPP, both in the absence and presence of initiator EBiB, was conducted across different solution temperatures. The first-order rate constant (k) was determined by the change of the absorption maximum (Figures 6a and S19) upon light-irradiated degradation.…”
Section: −•mentioning
confidence: 99%
“…The investigation into the thermodynamics of photocatalytic self-degradation of DPP was conducted to examine the catalysis mechanism . Specifically, the degradation of TDPP and PhDPP, both in the absence and presence of initiator EBiB, was conducted across different solution temperatures.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Moreover, these materials exhibit self-cleaning properties and, therefore, can be reused [6]. The adsorptive features of titania-activated carbon composites are especially beneficial for highly concentrated dye wastes since the dye molecules can inhibit the light harvesting by titania and cause photocatalyst poisoning that consequently reduces the photocatalytic performance [7,8]. Since titania is active under ultraviolet irradiation, its application requires special equipment and additional expenses.…”
Section: Introductionmentioning
confidence: 99%